Study on Predisposing Factors of Adolescent Dysmenorrhoea - Winarni, Winarni; Ropitasari, Ropitasari (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Dysmenorrhea is the most common complaint of menstrual pain during adolescence. Relevant risk factors for this condition include early menarche (<12). At this age, the reproductive organs have not fully developed, and the narrowing of the cervix can lead to pain during menstruation. The duration of menstruation may be influenced by continuous uterine contractions, which interrupt blood flow to the uterus. The length of the menstrual cycle plays a role in this, as a longer cycle leads to the release of more prostaglandins, causing pain. A family history of dysmenorrhea is an unmodifiable risk factor. This study aims to identify the predispositional factors that affect dysmenorrhea. The research design used is an analytical survey with a cross-sectional approach, which is a study aimed at exploring the correlation between causative factors and their effects, conducted simultaneously. The population consists of all students who experience menstrual pain. The sampling method used in this study was simple random sampling. The results show that the majority of subjects experienced dysmenorrhea, with 44 subjects (60,3%). Conclusion, there is a relationship between family history and exercise habits with the occurrence of primary dysmenorrhea, while no relationship was found between menarche age, menstrual duration, and nutritional status with the occurrence of primary dysmenorrhea.